2007
DOI: 10.1097/mcp.0b013e328010a890
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal asthma

Abstract: Nocturnal symptoms in asthma are frequently underdiagnosed. Obstructive sleep apnea may be prevalent in nocturnal asthma. The Gly16 polymorphism of the beta2-receptor is common in nocturnal asthma. Gastric suppression treatment in patients with both gastroesophageal reflux disease and nocturnal asthma improved the peak expiratory flow rate. Continuous positive airway pressure improves nocturnal symptoms but not lung function tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 37 publications
1
20
0
3
Order By: Relevance
“…The recurrent upper airway obstruction might cause reflex bronchoconstriction by stimulating neural receptors in the pharyngeal region or by generating negative intrathoracic pressure. 9,20 Another plausible explanation relates to gastrooesophageal reflux (GOR); it is known that the large intrapleural pressure swings during apnoeic episodes facilitates GOR, 21 and GOR is a potential trigger of asthma that may occur even without oesophageal symptoms. 22 Recently, studies have shown that OSA is associated with systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recurrent upper airway obstruction might cause reflex bronchoconstriction by stimulating neural receptors in the pharyngeal region or by generating negative intrathoracic pressure. 9,20 Another plausible explanation relates to gastrooesophageal reflux (GOR); it is known that the large intrapleural pressure swings during apnoeic episodes facilitates GOR, 21 and GOR is a potential trigger of asthma that may occur even without oesophageal symptoms. 22 Recently, studies have shown that OSA is associated with systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies that have explored the relationship between OSA and asthma have focused on the prevalence of snoring and OSA symptoms in patients with asthma. [6][7][8][9] Both obesity and OSA act to aggravate existing asthma making it more difficult to control symptoms. 10 However, to our knowledge, no study has directly addressed the reverse relationship -i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Although these nocturnal events are considered important in childhood asthma, their significance remains unclear due to a paucity of literature regarding this topic, in part due to the fact that most publications investigating nocturnal asthma have focused on adults (e.g., [2][3][4][5] ). Studies in children have examined the prevalence of nocturnal asthma [6][7][8][9][10][11] , associations with nocturnal asthma and sleep quality 10 and other factors associated with nocturnal asthma 9,[12][13][14][15] , but all of these studies were of short duration (≤7 days) or cross-sectional.…”
Section: Introductionmentioning
confidence: 99%
“…However, another study by Chugh et al found that clinically stable children with asthma often failed to report nocturnal symptoms despite objective daytime hypersomnia (36). Similarly, in a large cross-sectional survey, 40% of asthmatics did not report nocturnal symptoms, although the authors do not clearly state whether such symptoms were actually present (37). It has also been found that nocturnal symptoms are frequently missed by clinicians (38,39).…”
Section: Discussionmentioning
confidence: 99%